PENGARUH PEMBERIAN EKSTRAK DAUN BINAHONG (ANREDERA CORDIFOLIA (TEN.) STEENIS) DALAM AIR MINUM TERHADAP PERFORMA BROILER - Etha ‘Azizah Hasiib; Riyanti .; Madi Hartono (JURNAL ILMIAH PETERNAKAN TERPADU, 2015)
The purpose of this study were to 1) investigate the effects of heartleaf maderavine madevine (Anredera cordifolia (Ten.) Steenis) extract in water on performance of broiler 2) determine the optimal dose of heartleaf maderavine madevine leave extract in water on performance of broiler. This research use Completely Randomized Design (CRD), with 5 treatments (0 mg heartleaf maderavine madevine exract/kg bw, 100 mg heartleaf maderavine madevine exract kg bw, 150 mg heartleaf maderavine madevine exract /kg bw, 200 mg heartleaf maderavine madevine exract /kg bw, and 250 mg heartleaf maderavine madevine exract kg bw) and 4 replications. The material used 100 broilers age 15 days and was carried out for 14 days. Polynomal orthogonal test done if there is a signification variable. Based on result showed that the treatments did not provide significant effect on performance of broiler.